ARE THERE RACIAL/ETHNIC DISPARITIES IN VA PTSD TREATMENT RETENTION?. Issue 6 (24th November 2014) - Spoont, Michele R.; Nelson, David B.; Murdoch, Maureen; Sayer, Nina A.; Nugent, Sean; Rector, Thomas; Westermeyer, Joseph
<x xml:space="preserve">Abstract</x> Background Chronic posttraumatic stress disorder (PTSD) can result in significant social and physical impairments. Despite the Department of Veterans Affairs' (VA) expansion of mental health services into primary care clinics to reach larger numbers of Veterans with PTSD, many do not receive sufficient treatment to clinically benefit. This study explored whether the odds of premature mental health treatment termination varies by patient race/ethnicity and, if so, whether such variation is associated with differential access to services or beliefs about mental health treatments. Methods Prospective national cohort study of VA patients who were recently diagnosed with PTSD (n = 6, 788). Self‐administered surveys and electronic VA databases were utilized to examine mental health treatment retention across racial/ethnic groups in the 6 months following the PTSD diagnosis controlling for treatment need, access factors, age, gender, treatment beliefs, and facility factors. Results African American and Latino Veterans were less likely to receive a minimal trial of pharmacotherapy and African American Veterans were less likely to receive a minimal trial of any treatment in the 6 months after being diagnosed with PTSD. Controlling for beliefs about mental health treatments diminished the lower odds of pharmacotherapy retention among Latino but not African American Veterans. Access factors did not contribute to treatment retention disparities. Conclusions Even in safety‐net healthcare systems like VA, racial and ethnic disparities in mental health treatment occur. To improve treatment equity, clinicians may need to more directly address patients' treatment beliefs. More understanding is needed to address the treatment disparity for African American Veterans.